COVID-19 and end stage renal disease treatment modalities in the United States - John D Sullivan (Archives of Renal Diseases and Management - Peertechz Publications, 2021)
From the establishment of nearly universal health coverage for end stage renal disease in 1972 to 2021, the primary treatment modality has been in-center hemodialysis despite significant advances in home therapies such as peritoneal dialysis and home hemodialysis.